Dissimilar weld failure: A forensic analysis to determine primary failure mechanisms. (September 2022) - Yin, Yanting; Rumman, Raihan; Sarvghad, Madjid; Bell, Stuart; Will, Geoffrey; Clegg, Richard E.; Perilli, Egon; Rapagna, Sophie; Lewis, David A.; Steinberg, Theodore A.; Andersson, Gunther G.
Highlights: Forensic analysis of a a low-pressure CO2 receiver in concentrated solar power plants. Failure of a weld through thermal cycling conditions. 3-D analysis of cracks through micro-computed tomography (micro-CT). Stress/strains produced due to thermal expansion mismatch in dissimilar metal welds. Abstract: Solar receivers are an integral part of a concentrated solar power plant and commonly utilise tubular structures to absorb solar energy and transfer the heat into a heat transfer fluid. These systems often contain dissimilar materials joined through welds which are exposed to cyclic temperatures, which can be a locus of failure. A systematic forensic analysis was carried out on a low-pressure CO2 receiver that had developed extensive cracking. Microstructural characterisation using micro-computed tomography was performed to understand the failure mechanism in an area adjacent to a welded section of the two dissimilar alloys Haynes 230 and 253 MA. An electrolytical oxalic acid etch showed grain boundary damage from oxidation. Grain boundary damage through oxidation was confirmed with SEM and energy dispersive X-ray spectroscopy (EDX) analysis as the likely metallurgical degradation mechanism which, combined with thermally induced stress cycles led to the failure of the weaker stainless-steel tube adjacent to the weld.